Long-term storage of C-141 reference strain of melioidosis agent (Burkholderia pseudomallei) - E. A. Artemeva; L. A. Melnikova; A. P. Rodionov (Ветеринария сегодня)
Melioidosis is a highly dangerous infectious disease caused by Hazard Group II bacteria Burkholderia pseudomallei, against which specific prevention and treatment tools have not been developed yet. Both humans and animals suffer from the disease. Previously the disease was prevalent in Southeast Asia regions, but currently is reported almost in all continents of the globe. Potential possibility of the agent introduction to the Russian Federation as well as the risk of malevolent use of this agent as a tool of bioterrorism dictates the need for storage of this pathogen in the microorganism collections to study its properties, develop and test diagnostic, detection and identification means. Microorganism Collection Laboratory of the FSBSI “FCTRBS-ARRVI” is responsible for storage and preservation of Burkholderia pseudomallei С-141 reference strain, submitted by Federal State Scientific Institution “Russian Research Anti-Plague Institute “Microbe” under the Rospotrebnadzor (Saratov city) for research purposes in 1983 and as a back-upstrain in case of its loss by other collections. The purpose of the work was to study the preservation of biological properties of freeze-dried Burkholderia pseudomallei С-141 strain after 11 years of storage. It was established that under optimal storage conditions (temperature of 4–8 °С, skimmed milk as a cryoprotectant) the strain remained viable and retained its biological properties during the wholeo bservation period. С-141 strain showed saccharolytic, oxidase, catalase and proteolytic activities, did not generate hydrogen sulphide, which is consistent with the melioidosis agent biochemical features. The strain was refreshed by passaging in golden hamsters and Burkholderia culture was isolated and freeze-dried. Burkholderia pseudomallei С-141 freeze-driedstrain was tested for quality parameters, records were made and the strain was deposited.